Analysis Of Understanding Of Sexual Violence In University Campus - Wibowo, Syifa Sofia; Rimawati, Eti; Kusumawati, Nugraheni; Ashari, Ayu (Poltekkes Kemenkes Semarang, 2025)
According to a survey conducted by Kemendikbudristek, the majority of sexual violence took place in universities, 65 incidences of sexual violence occurred in universities in July 2023. The research sample was students of one of the campuses in the city of Semarang and 468 people completed it. This study aims to determine the understanding of lecturers, teaching staff and students at campus regarding sexual violence. This study is an analytical observational study using a cross-sectional research approach and a descriptive research design using primary data. The respondents were mostly students (97%) from the Faculty of Health (24.3%) and female (61.5%). The majority of respondents (97.9%) claimed to have heard of sexual violence and to be familiar with its concept. Non-physical sexual violence, including verbal abuse and sensual look, was selected as a form of sexual assault by 268 respondents (57.3%). The majority of respondents (97.9%) reported having heard, witnessed, or experienced sexual violence also the incident happened off campus. The reason respondents not report sexual harasseent because respondents believe that sexual violence cases are private issues that should not be disclosed to others. 88.5% respondents of the sample answered its crucial to avoid sexual violence on theuniversity campus. Among the preventative measures that university campus may implement to stop sexual violence, respondents recommended a safe and private reporting system (45.3%). In order to report or handle sexual violence cases, respondents recommended a hotline that is available at all times (22.4%).